2014
DOI: 10.1177/0020764014535756
|View full text |Cite
|
Sign up to set email alerts
|

Logistic regression analysis of psychosocial correlates associated with recovery from schizophrenia in a Chinese community

Abstract: Preliminary findings suggest that adopting salient life roles personally is important to recovery and that this component should be incorporated into mental health services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…The current findings have implications for community interventions, therapy and case management of patients with schizophrenia. The findings are in alignment with the recovery paradigm ( 7 ), that recovery is multi-faceted, including both clinical remission and broader social functioning ( 9 ). Clinicians could support patients’ recovery through enhanced coping, better management of symptoms ( 11 ), and social functioning ( 12 ), which are related to QOL.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…The current findings have implications for community interventions, therapy and case management of patients with schizophrenia. The findings are in alignment with the recovery paradigm ( 7 ), that recovery is multi-faceted, including both clinical remission and broader social functioning ( 9 ). Clinicians could support patients’ recovery through enhanced coping, better management of symptoms ( 11 ), and social functioning ( 12 ), which are related to QOL.…”
Section: Discussionsupporting
confidence: 73%
“…Functional impairment is high, leading to lost wages and work impairment, with related personal, societal, and economic burdens ( 5 , 6 ). More mental health services are adopting the recovery paradigm ( 7 ), focusing on rehabilitation ( 8 ). Recovery is multi-faceted ( 9 ), it encompasses hopefulness and empowerment and the pursuit of life goals, aspirations, and valued social roles ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Substantially the same predictors were found for FR (Helldin et al 2007). As was found in the foregoing studies, Tse et al (2015) also found that the chance of recovery increases with age, but these authors did not distinguish between SR and FR.…”
Section: Introductionsupporting
confidence: 74%